PTU-043 Capsule Endoscopy Retention; Is Prediction Without A Patency Pre-study Possible?. (9th June 2014) - Makins, R; Hopkins, R
Abstract : Introduction: Small intestinal capsule endoscopy (CE) is used to investigate occult gastrointestinal bleeding, iron deficiency anaemia, to evaluate the small intestine for Crohn's disease (CD), polyposis syndromes or complications of NSAID use. The only significant complication is capsule retention, either long term or transient, potentially leading to luminal obstruction. The Patency Capsule can be used prior to CE to confirm the likelihood of safe passage however is only for use in conjunction with the system by Given Imaging (Diagmed UK, Personal communication). We use Mirocam CE equipment (Intromedic). Consequently reliance must be placed on radiological studies along with clinical evaluation when assessing the risk of retention. The aim of this study was to determine, in patients where capsule retention had occurred in the setting of a previously reported normal radiological study, whether retrospective review of the radiology could identify stricturing disease and therefore determine whether retention could have been predicted with prior radiological imaging alone. Methods: We reviewed records of all patients who had undergone CE in Gloucestershire since the inception of the local service in 2008. Identified all patients in whom capsule retention occurred. Defined capsule retention as occuring in patients where a stricturing lesion was seen, the capsule appeared not to pass the lesion and colonic mucosa was not positively identified. We retrospectively reviewed any relevant radiological studies performed prior to the CE to determine whether, with hindsight, abnormalities could be identified that would have significantly increased the risk of capsule retention. Results: 465 CE performed locally in Gloucestershire since 2008. CE retention occured above a stricture in 6 (4 male, mean age 45, range 27–61). Indications for CE abdominal pain +/- anaemia. In 5 the strictures were thought to be secondary to CD (past history of CD in 2 only), in 1 due to NSAID use. No stricturing lesions had been identified previously on either barium follow through (2) or cross sectional (CT) imaging (4). 4 studies had been performed locally, 2 by other providers, reported by non-specialist radiologists. On retrospective review significant stricturing lesions were seen on all studies, findings contraindicating CE. Conclusion: CE is a safe and widely used tool. The risk of capsule retention increases in the setting of Crohn's disease. We have shown that in cases where capsule retention occurred in our institution, where prior radiology was reported as normal, stricturing lesions could be positively identified when reviewed retrospectively by a specialist radiologist. We conclude that thorough radiological assessment is adequate to predict capsule retention and patency studies prior to CE are therefore unnecessary. Disclosure of Interest: None Declared.